The resilience of Balinese Tourism News during Post Covid-19 Pandemic - Daniel Susilo; Lu Hui Chen (CV. AFDIFAL MAJU BERKAH, 2023)
Tourism is like the industry and realistic example how to build a utopia. Tourism destination is like a real heaven to some people where they relax themselves and taking temporary happiness even though it’s costy. However, in Bali, it isn’t always looks like green grass. With analysis Google news traffic, we can see connected narrations through different public statement even though the news site is diverse. As a result, Bali is facing a new Divide et Impera circumstances using UU ITE tools.